Critical Analysis of Toll Road Investment Through A Systematic Literature Review Approach: Trends, Challenges, and Opportunities - Rio Rizqi Septiawan; Oei Fuk Jin (Eduvest - Journal of Universal Studies, 2026)
Toll Road Investment is a key strategy in transportation infrastructure development aimed at improving connectivity, logistics efficiency, and economic growth. However, financing complexity, regulatory uncertainty, and socio-political risk dynamics make this investment face serious challenges. Twenty scientific articles published in Q1–Q3 between 2019–2024 were evaluated based on their study focus, key findings, geographic context, and journal rankings. The research results indicate that toll road investment trends are undergoing a significant transformation, marked by the dominance of Public–Private Partnership (PPP) schemes, the integration of digital technology, and a lifecycle-based management approach. Meanwhile, the key challenges identified include a weak regulatory framework, financial risks, limited government capacity, and minimal stakeholder involvement. Conversely, opportunities can be leveraged through strengthening project governance, utilizing innovative contract models, and adopting risk- and sustainability-based performance evaluation systems. These findings are expected to provide theoretical and practical contributions to academics, policymakers, and investors in designing more adaptive and sustainable toll road investment strategies in the future